2022
DOI: 10.1136/bmjopen-2021-051777
|View full text |Cite
|
Sign up to set email alerts
|

Chronic high-altitude exposure and the epidemiology of ischaemic stroke: a systematic review

Abstract: IntroductionAbout 5.7% of the world population resides above 1500 m. It has been hypothesised that acute exposure to high-altitude locations can increase stroke risk, while chronic hypoxia can reduce stroke-related mortality.ObjectiveThis review aims to provide an overview of the available evidence on the association between long-term high-altitude exposure and ischaemic stroke.DesignA systematic review was performed from 1 January 1960 to 1 December 2021 to assess the possible link between high-altitude expos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
37
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(39 citation statements)
references
References 49 publications
0
37
1
1
Order By: Relevance
“…Although the ramifications of high-altitude hypoxia might have been well appreciated [3,[19][20][21][22][23], there have been few reports on the influence of high-altitude hypoxia on anesthesia management. Compared with previous studies, [8,[24][25][26][27] the occurrence of moderate hypoxia was more common in the nasal cannula group (47.2%).…”
Section: Discussionmentioning
confidence: 99%
“…Although the ramifications of high-altitude hypoxia might have been well appreciated [3,[19][20][21][22][23], there have been few reports on the influence of high-altitude hypoxia on anesthesia management. Compared with previous studies, [8,[24][25][26][27] the occurrence of moderate hypoxia was more common in the nasal cannula group (47.2%).…”
Section: Discussionmentioning
confidence: 99%
“…As altitude increases, the amount of gas molecules in the air decreases, resulting in a drop in barometric pressure and partial pressure of oxygen. People who ascend to high altitude and exposed to hypobaric hypoxia will suffer a significant decrease of arterial and tissue partial pressure of oxygen in the brain ( 9 ). A series of physiological responses will be triggered.…”
Section: Introductionmentioning
confidence: 99%
“… 11 19 However, stroke epidemiology at high altitudes has not been extensively studied, especially in areas with 4000 m and over. 20 Therefore, a household survey was conducted to explore the prevalence of stroke, the detection rate of individuals at high risk of stroke and the risk factors for stroke among residents living in the Tibetan Plateau of China (2000–4500 m). The results could provide epidemiological data for the primary prevention of stroke in plateau areas.…”
Section: Introductionmentioning
confidence: 99%
“…A study reported that the stroke prevalence in the Northeast was almost three times higher than in the Southwest 11 19. However, stroke epidemiology at high altitudes has not been extensively studied, especially in areas with 4000 m and over 20. Therefore, a household survey was conducted to explore the prevalence of stroke, the detection rate of individuals at high risk of stroke and the risk factors for stroke among residents living in the Tibetan Plateau of China (2000–4500 m).…”
Section: Introductionmentioning
confidence: 99%